Role of photosynthesis and stomatal conductance on the long-term rising of intrinsic water use efficiency in dominant trees in three old-growth forests in Bosnia-Herzegovina and Montenegro - Palandrani C; Motta R; Cherubini P; Curović M; Dukić V; Tonon G; Ceccon C; Peressotti A; Alberti G (iForest - Biogeosciences and Forestry, 2021)
Old-growth forests have an important role in maintaining animal and plant diversity, are important carbon (C) reservoirs and are privileged sites to study long-term plant physiological responses, long-term forest dynamics and climate change impact on forest ecosystems. Several studies have highlighted how old-living trees undergo age-related declines with hydraulic limitations and reduction in photosynthesis, though some recent works have suggested that such a decline is not always observed. Our study aims at understanding the role of atmospheric CO2 increase on tree C uptake and stomatal conductance (gs) in old-living trees by analysing the long-term patterns of tree growth and intrinsic water use efficiency (iWUE) in three old-growth forests in the Balkans (Bosnia-Herzegovina and Montenegro), using dendrochronology and isotopic analysis. We hypothesised a long-term increase in iWUE in the studied old-growth forests, mostly related to enhanced photosynthesis rather than reduced stomatal conductance. Tree cores were sampled from dominant silver fir (Abies alba Mill.) trees in each forest. Tree-ring widths were measured and basal area increments (BAI) were assessed for each sampled tree and, from the six longest chronologies, five decades were chosen for cellulose extraction, its isotopic analysis (δ13C, δ18O), iWUE and leaf water 18O evaporative enrichment above the source water (Δ18OL) determination. We observed a continuous and significant increase in iWUE from 1800 to 2010 in the sampled dominant trees at all the three old-growth forests. Our BAI data and our estimates of Δ18OL across the study period support the idea that enhanced photosynthesis rather than reduced stomatal conductance is the major driver of the measured iWUE increase. Thus, our results support some recent findings challenging the hypothesis that iWUE in forests is primarily the result of a CO2-induced reduction in stomatal conductance as well as the so called hydraulic limitation hypothesis.